Exhibition Conference Service Economics in China: Trends, Challenges, and Opportunities - Song Hui (Research Parks Publishers, 2026)
The exhibition and conference service industry has emerged as a fundamental component of China's contemporary service economy. In this article, a complete investigation into the development of the industry, its function in the economy, and its potential future trajectory is presented. The historical evolution of exhibition economics in China, the incorporation of conferences into the service economy, and the interaction between globalisation, digitalisation, and sustainability are all topics that are investigated in this book. The report shows potential for regional diversification, technological innovation, and international collaboration by analysing constraints such as talent shortages, infrastructural needs, and external shocks. These challenges are evaluated in order to highlight opportunities. The discussion places an emphasis on the industry's ability to affect global service economics as well as its contribution to the modernisation of China's economy.